Al-Lughah al-Malāyuwīyah wa takwīn al-Islām al-Indūnīsī: Naẓrah tārīkhīyah ijtimā‘īyah - Jajat Burhanudin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2014)
The Malay language is of great importance in understanding Indonesian society and history. As the root of Indonesia’s national language, Bahasa Indonesia, the language has become part and parcel of the social-political and cultural formation of the diverse communities throughout Indonesia. Also, the role of the Malay language in Indonesian nation building proceeded alongside the historical course of Islamic development there. In line with the development of Islam in parts of Indonesia and the Southeast Asia region at large, Malay emerged as a lingua franca that was widely used as a media of social interaction, political diplomacy, commerce and, more importantly, Islamic expression. This article discusses the history of the Malay language in relation to its role as the language of Indonesian Muslims. The article also examines the contribution that the language has made, through the course of history, in uniting the people into a single nation-state—Indonesia.DOI: 10.15408/sdi.v21i3.1219